Mosukuru: Sebagai Wujud dari Metode Pencatatan Akuntansi oleh Pedagang di Pasar Tradisional Gorontalo - Mohamad Anwar Thalib; Widy Pratiwi Monantun (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2022)
This study aims to construct the method of accounting records by traders in traditional markets. This study uses an Islamic paradigm with an Islamic ethnomethodology approach. There are five stages of data analysis; amal, ilmu, iman, informasi wahyu, and ihsan (amiiin). The results of the study find that there are two methods of accounting records; first, record expenses on paper and in memory; second, record profits on paper and in memory. Both methods are driven by gratitude (sukuru) for the income given by God.